Coupled chemo-mechanical modeling of fracture in polycrystalline cathode for lithium-ion battery. (April 2020) - Singh, Avtar; Pal, Siladitya
Abstract: A thermodynamically consistent multi-physics framework has been developed to understand the chemo-mechanical interplay towards fracture behavior of polycrystalline microstructure along with the current collector. Adopting non-equilibrium thermodynamics, and considering bulk and interfaces as separate systems, the coupled governing equations are derived. The proposed framework accounts the plastic deformation of the host lattice and the substrate. A chemo-mechanical cohesive zone model (CZM) has been formulated to simultaneously capture the decohesion and transport across grain boundaries, while classical CZM is used between the cathode/substrate interface. Using numerical framework, grain-boundary width is initially calibrated to ensure transport of Li-ions through intact grain boundaries. The proposed numerical scheme has been verified with semi-analytical model for cylindrical cathode particle in the presence of an interface. Further, thin film polycrystalline cathode along with current collector has been examined to explore the role of various interactions (one way or two way) between the diffusion and stresses on the emergent voltage profile for an electrochemical cycle. In particular, the chemical and mechanical driving forces have been investigated together with evolution of grain boundary fracture and their consequences on the insertion/extraction of Li-ions from the host lattices. In addition, we address the mechanical failure and attendant voltage profiles for various microstructural and electrochemical parameters (i.e., grain size and charge rate). The present framework can provide better design perspective for the development of heterogeneous electrode system with improved mechanical integrity under fully coupled chemo-mechanical environment. Highlights: Coupled multi-physics modeling of polycrystalline cathode is developed. Fracture of grain boundaries and plastic deformation of electrode are addressed. Chemo-mechanical driving forces with fracture influence the extraction of Li-ions. Increase in grain size hinders the diffusion of Li-ions due to tortuous crack path. Higher charge rate restricts plastic region and arrests grain boundary fracture.